Prediction Of Demand For Air Transport Services In Haluoleo Airport - Kendari (International Journal of Psychosocial Rehabilitation, 2020)
This paper will analyze the number of passengers and make predictions about the number of passengers who will use the Haluoleo airport in Kendari. Several approaches for forecasting air transport passengers at Haluoleo Airport - Kendari are deemed necessary to facilitate the selection of realistic projection values, namely forecasting using the method Regression analysis with several variable simulations, forecasting using passenger growth rates for historical periods, forecasting with a linear model where time functions as an independent variable. From the results of this study, the results of forecasting transport passengers from 2014 to 2035.